Thunbergia laurifolia leaf extract mitigates cadmium toxicity in rats - Werawan Ruangyuttikarn (2018)
Thunbergia laurifolia (TL) is a medicinal herb traditionally used in Thailand for centuries as an antidote for several poisons. To test whether the TL could mitigate toxicity of cadmium, we subjected Wistar rats pre-fed with and without crude or partially purified extract of the TL to cadmium challenge. Physiopathology of the rats and histopathological examination of the kidney and liver revealed that pre-fed rats with the TL reduced toxicity signs and organ damages caused by cadmium. The extracts did not alter the cadmium concentrations in blood or urine. Nuclear magnetic resonance spectroscopy detected aromatic and glycoside compounds in the TL extract which may have been the mechanism of the observed mitigation effects of the extract. This finding suggests that TL herbal tea may be useful in humans with unavoidable exposure to environmental cadmium.